Knowledge and practices of using antibiotics by patients with acute respiratory infections (One Health & Risk Management, 2023)
Introduction. Excessive and inappropriate antibiotic (AB) consumption is associated with the development of antibiotic resistance (AR). Insufficient knowledge and irrational practices in the use of AB for acute respiratory infections (ARI) by patients contribute to the development of AR. Aim: to assess the knowledge and practices of AB use in patients with ARI in order to identify educational needs.Material and methods. The study included 393 patients with ARI. The standardized Happy Audit-2 questionnaire was applied. Complaints, the frequency of ARI occurrence, administered AB treatment, AB acquisition method, AB compliance, knowledge about AB, and AB resistance were assessed.Results. AB were used by 40.3% of the patients. Antibiotic treatment was recommended by a doctor in 87.6% of cases, taken independently by 5.6%, recommended by a pharmacist in 5.0%, and recommended by relatives in 1.9% of cases. AB were obtained without a prescription in 6.3% of cases, and household reserves were used in 20.8% of cases. Patients were compliant with antibiotic treatment in 89.7% of cases but 10.3% of respondents did not adhere to the prescribed duration/dosage. 26.7% of respondents believed that AB were effective against viral infections, and 13.8% believed they were harmless to the human body. In 24.1% of cases, respondents were unaware of the adverse effects of AB, including the development of bacterial resistance in 29.7% of cases.Conclusions. Insufficient knowledge about the effects of antibiotics and irrational usage practices, including self-medication, emphasize the need for strengthening awareness and education measures for potential antibiotic users.